Characterization of VHF radar observations associated with equatorial Spread F by narrow-band optical measurements - Sekar, R.; Chakrabarty, D.; Narayanan, R.; Sripathi, S.; Patra, A.K.; Subbarao, K.S.V. (My University, 2004)
The VHF radars have been extensively used to investigate the structures and dynamics of equatorial Spread F (ESF) irregularities. However, unambiguous identification of the nature of the structures in terms of plasma depletion or enhancement requires another technique, as the return echo measured by VHF radar is proportional to the square of the electron density fluctuations. In order to address this issue, co-ordinated radar backscatter and thermospheric airglow intensity measurements were carried out during March 2003 from the MST radar site at Gadanki. Temporal variations of 630.0-nm and 777.4-nm emission intensities reveal small-scale ("micro") and large-scale ("macro") variations during the period of observation. The micro variations are absent on non-ESF nights while the macro variations are present on both ESF and non-ESF nights. In addition to the well-known anti-correlation between the base height of the F-region and the nocturnal variation of thermospheric airglow intensities, the variation of the base height of the F-layer, on occasion, is found to manifest as a bottomside wave-like structure, as seen by VHF radar on an ESF night. The micro variations in the airglow intensities are associated with large-scale irregular plasma structures and found to be in correspondence with the "plume" structures obtained by VHF radar. In addition to the commonly observed depletions with upward movement, the observation unequivocally reveals the presence of plasma enhancements which move downwards. The observation of enhancement in 777.4-nm airglow intensity, which is characterized as plasma enhancement, provides an experimental verification of the earlier prediction based on numerical modeling studies.
Keywords: VHF radars; Equatorial Spread F(ESF); Equatorial ionosphere; MST radar; Airglow and aurora; Ionspheric irregularities